From Tradition to Transformation: Community-Based Cultural Practices in Urban Indonesia - Nofandi, R. Adang; Isnaini, Titi (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines how cultural practices function as drivers of social transformation in a multicultural urban context. Focusing on Rumah Cinwa, a community-based cultural initiative in Depok, Indonesia, the research explores how traditional art particularly Wayang Potehi is reinterpreted and mobilized to foster inclusive social relations. Using a qualitative field research approach, data were collected through interviews, observations, and document analysis. The findings indicate that Rumah Cinwa serves not only as a space for cultural preservation but also as an active platform for social interaction and transformation. Through collaborative performances and community-based activities, the group transforms an ethnic-specific art form into a shared cultural medium that encourages participation across diverse groups. This process reflects cultural hybridity and contributes to social cohesion. Religious moderation emerges as an outcome of sustained intercultural interaction rather than as a primary agenda. This study argues that community-driven cultural practices play a crucial role in shaping inclusive societies in contemporary Indonesia.